Loess Plateau Cropland: Evolution and Ecological Impacts over Four Millennia - Tao Huang; Shaoshan An; Wanyun Huang; Baoyuan Liu (Land)
The Loess Plateau (LP), the cradle of Chinese civilization, has a long history of agricultural activities closely linked to ecological changes. This study addresses a fundamental question: what was the maximum sustainable cropland area threshold for the LP prior to modern soil and water conservation measures? To answer this, we analyzed the historical data to investigate changes in the cropland area and their ecological impacts over the past 4000 years, with the specific aim of examining the long-term interactions between land exploitation and the ecosystem that defined sustainable thresholds. Three key stages of cropland area development were identified: slow growth (2000–500 BC), a fluctuating phase (500 BC–1000 AD), and rapid expansion (1000–2000 AD). During the slow-growth and rapid-expansion stages, the cropland areas were estimated at 34.9 ± 23.4 and 117.9 ± 34.1 thousand km2, with growth rates of 2.9 and 8.7 thousand km2/100 years, respectively, while the fluctuating period stabilized at 62.1 ± 18.1 thousand km2. Population growth was the primary driver of cropland expansion (56.9%), followed by agricultural technology and policy adjustments (27%) and climate change (16.1%). Particularly over the past 1000 years, climate deterioration and a population surge due to the abolition of the poll tax accelerated cropland expansion, resulting in deforestation, intensified soil erosion specific to the LP, and frequent flooding of the lower Yellow River (YR). In contrast, during the fluctuating period, rapid social development did not lead to major ecological issues, suggesting that moderate cropland expansion can balance social development and ecological sustainability. Based on the historical conditions, without modern soil and water conservation measures, this study determined that the upper limit of the cropland area during the fluctuating period (80.2 thousand km2) is the maximum sustainable cropland area for the LP, establishing a scientific basis to guide future land-use strategies. Especially in the face of population pressure and climate deterioration, developing agriculture and adjusting policies to increase grain production will be essential to balance the ecological risks and maintenance of food security while remaining within this threshold. These findings offer insights into the agricultural history and ecological management of the LP and can serve as a reference for similar studies of other regions.